2014
DOI: 10.1002/adsc.201400102
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Partial Oxidation of Methane over Bimetallic Nickel‐f Block Element Oxide Nanocatalysts

Abstract: The partial oxidation of methane (POM) was studied over bimetallic nickel-f block element oxide nanocatalysts prepared by a modified sol-gel method. They proved to be active (conversion of methane, 50-70%) at a relatively low temperatures (550 and 650 8C) and highly selective towards synthesis gas production (selectivity, H 2 60-90% and CO 50-80%). The activity and selectivity depend on the surface basicity and size of the bimetallic oxide nanoparticles: lower particle size and higher basicity, enhanced activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 95 publications
2
19
0
Order By: Relevance
“…It is known from the literature that the addition of rare earth oxides inhibits catalysts deactivation. This fact can explain our nickel catalysts enhanced stability …”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…It is known from the literature that the addition of rare earth oxides inhibits catalysts deactivation. This fact can explain our nickel catalysts enhanced stability …”
Section: Resultssupporting
confidence: 57%
“…In our group, the synthesis of bimetallic oxides containing f ‐block elements (lanthanide and actinides) with other metals such as copper, nickel or calcium and the pursuit of catalytic applications to the valorization of primary pollutants are important goals that continue to be studied . In particular, nickel‐5 f elements oxides proved to be very active for the partial oxidation of methane (POM) and formation of syngas, whereas those containing calcium were very active for the formation of C 2 hydrocarbons (ethane, ethylene) , , , . Bimetallic oxides nickel‐based catalysts containing 4 f or 5 f block elements show also an unusual long stability in the gaseous stream that is a considerable advantage .…”
Section: Introductionmentioning
confidence: 99%
“…The good activity of Mn/Fe/O is in agreement with our previous study, in which we demonstrated that a mixture of Mn III and Mn IV coexists with a hematite phase. Also, as already reported, the surface basicity improved the catalyst oxidant behavior (Figure ) . Moreover, charge‐transfer transitions between iron d electrons and the manganese oxide conduction or valence bands were evidenced in the UV/Vis spectra by the redshift of the high energy band for Mn/Fe/O compared with that for Mn 2 O 3 (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Recent achievements emphasized that the surface basicity improve the catalyst's oxidant strength [53]. In order to confirm this, the catalysts basicity has been determined and correlated to the catalytic performances.…”
Section: Entrymentioning
confidence: 99%